Fenomena Urban Sprawl Jabodetabek - Asmi, Anisa Ulul; Juhadi, Juhadi; Indrayati, Ariyani (Edu Geography, 2018)
This research aims to (1) Assess spatial spatial pattern (2) Assess spatial process (3) Assess sptatial structure (4) Assess trends of constructed land (5) Produces books nonteks urban sprawl phenomenon of Jabodetabek. Object of research is the urban sprawl. Analysis of the data used is GIS map analysis and qualitative descriptive. The result of this research is (1) Land use change in Jabodetabek area shows an increase of 6% of constructed land for 16 years, then the spread of urban areas to grow following the existence of a network roads, the study in terms of urban sprawl process Jabodetabek included into the type of ribbon development. The tendency of the development of land is built to the south of the Bogor city. The average yield of all aspects of the teacher ratings indicate the percentage of 81.6% with a decent criteria and showed excellent predicate. Thus nonteks book preserving the urban sprawl phenomenon of Jabodetabek decent used as the enrichment of knowledge and can be used as teaching materials geography. Penelitian ini bertujuan (1) Mengetahui pola keruangan (2) Mengetahui proses keruangan (3) Mengetahui struktur keruangan (4) Mengetahui kecendrungan lahan terbangun (5) Tersusunya buku nonteks âfenomena urban sprawl Jabodetabekâ. Obyek penelitian ini adalah urban sprawl. Analisis data yang digunakan adalah analisis peta SIG dan deskriptif kualitatif. Hasil penelitian adalah (1) Perubahan penggunaan lahan wilayah Jabodetabek menunjukkan peningkatan lahan terbangun sebesar 6% dalam kurun waktu 16 tahun, kemudian persebaran kawasan perkotaan tumbuh mengikuti keberadaan jaringan jalan, sehingga ditinjau dari prosesnya pola lahan terbangun yang terbentuk termasuk kedalam tipe ribbon development. Kecendrungan perkembangan lahan terbangun yaitu ke arah selatan yaitu Kota Bogor (2) Hasil rata-rata penilaian semua aspek oleh guru menunjukan persentase sebesar 81.6% dengan kriteria layak dan menunjukan predikat baik. Dengan demikian buku nonteks Fenomena Urban Sprawl Jabodetabek layak digunakan sebagai buku pengayaan pengetahuan.